The scream of the haunted mask [compact disc, unabridged] - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2009)
Carly Beth tries to resist calls from an evil mask she defeated a year ago during Halloween while working at an after-school program at the Tumbledown Farms, where a stable of horses and a farm hand died tragically a century ago.